Cooking for a fast metabolism : eat more food and lose more weight - Pomroy, Haylie; Adamson, Eve (Houghton Mifflin Harcourt, 2020)
"A metabolism-boosting cookbook from Haylie Pomroy, the #1 New York Times best-selling author of The Fast Metabolism Diet"--